How does cultural norms influence entrepreneurial intention?: a cross cultural study - Sánchez García, José Carlos (2018)
Entrepreneurial Intention is commonly attributed to the interaction of cultural values and attitude; however, cultural values vary according to the context in which they are developed. The following study intends to show how Subjective Norms affect intentions of self-employment, as both, a direct factor and mediated through attitudinal values: Perceived Behavioral Control and Desirability, within a cross-cultural framework. A sample of 736 students from four different countries: Spain, Portugal, Mexico and India were used. Results yielded a direct relationship between Subjective Norm and Intention in all countries, except India. When mediated through attitude, the relation becomes stronger, even more when it’s through Desirability, except in Portugal, which the relationship is stronger directly through Social Norms. India does not show a relationship between Perceived Behavioral Control and Intention. Conclusions show that the influence of culture on intention, effectively, varies by context.